Engineering and Economic Analysis of the Synthesis of Fluoride Tin Oxide Film Production - Aziz, Tsabbit Aidil; Fariansyah, Ruslan (جامعة الوادي - university of el oued, 2020)
The purpose of this study was to analyze the Fluoride Tin Oxide (SnO2/F) production in home-scale industry in engineering point of view and economic evaluation perspective. This material is considered due to its wide range of energy-related applications. Evaluation of the SnO2/F production in engineering perspective is conducted from the selection of the most economical process, mass balance calculation, to the adaptation in the commercially available apparatuses. Evaluation of the production from the economic point of view is done by calculating economic parameters: Gross Profit Margin, Internal Rate Return, Payback Period, Cummulative Net Present Value, Profitability Index, and Breakeven Point. In short of the production process, we used the pure tin (as the metal precursor) and ammonium fluoride (as the source of Flouride for doping). The engineering point of view showed that the process is able to produce conductive glass that can be used as the active electrode substrate in the solar cell. Economic evaluation showed that the process is profitable, confirmed by the positive values from all economic parameters. However, for some cases that are compared to the market and the local bank interest, the process is not attractive for investor. Thus, to make them attractive, support from government or corporate social responsibility is require
Article
Keywords: energy, tin oxide production, conductive glass